2021
DOI: 10.1186/s40323-021-00199-0
|View full text |Cite
|
Sign up to set email alerts
|

A semi-analytical coupled simulation approach for induction heating

Abstract: The numerical simulation of the induction heating process can be computationally expensive, especially if ferromagnetic materials are studied. There are several analytical models that describe the electromagnetic phenomena. However, these are very limited by the geometry of the coil and the workpiece. Thus, the usual method for computing more complex systems is to use the finite element method to solve the set of equations in the multiphysical system, but this easily becomes very time consuming. This paper dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…From a practical point of view, the latest proposals of the scientists of the Kharkov National Automobile and Highway University (KhNAHU) to increase the intensity of the Lenz-Joule heat release in the metal of the object of processing are of interest [25,26]. The authors of [25] theoretically and experimentally substantiated the advisability of introducing ferromagnets into the design of inductor systems.…”
Section: Induction Heatingmentioning
confidence: 99%
See 1 more Smart Citation
“…From a practical point of view, the latest proposals of the scientists of the Kharkov National Automobile and Highway University (KhNAHU) to increase the intensity of the Lenz-Joule heat release in the metal of the object of processing are of interest [25,26]. The authors of [25] theoretically and experimentally substantiated the advisability of introducing ferromagnets into the design of inductor systems.…”
Section: Induction Heatingmentioning
confidence: 99%
“…From a practical point of view, the latest proposals of the scientists of the Kharkov National Automobile and Highway University (KhNAHU) to increase the intensity of the Lenz-Joule heat release in the metal of the object of processing are of interest [25,26]. The authors of [25] theoretically and experimentally substantiated the advisability of introducing ferromagnets into the design of inductor systems. It is shown that, in the presence of ferrite filling, there is a significant increase in the amplitudes of the excited currents and it is possible to increase the intensity of the induction process by more than ~ 1.5 times.…”
Section: Induction Heatingmentioning
confidence: 99%
“…Numerical modeling of the induction heating process can be difficult from the computational point of view, especially in the case of ferromagnetic materials. Article [9] is devoted to finding solutions for the coupled electromagnetic-thermal problem with higher computational efficiency. Therefore, the so-called semi-analytical modeling approach is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In the work by Bay et al [9], ferromagnetic nonlinear effects are taken into account, but only temperatures below the Curie temperature are considered and the effect of magnetic hysteresis is neglected. Areitioaurtena et al proposed an approximate solution based on a semianalytical modeling strategy [10,11]. In their work, an analytical electromagnetic approach is followed to solve the coupled electromagnetic-thermal problem by determining the initial model based on the harmonic approximation and performing the finite element solution.…”
Section: Introduction (Giriş)mentioning
confidence: 99%